PERKEMBANGAN DAN PROBLEMATIKA KURIKULUM PENDIDIKAN AGAMA ISLAM (PAI) DI INDONESIA DARI MASA KE MASA - Nurhasanah; Sukino, Arief (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2022)
This research was driven by changes in the national education curriculum in Indonesia which has undergone several changes and modifications. Along with the growth and development of science and technology in the realm of education, it requires our educational curriculum to adapt to current development. The curriculum of Islamic religious education or PAI also experiences development and keeps up with the times. This study seeks to reveal the development of the existing Islamic religious education curriculum in Indonesia and the problems faced in each era in which the curriculum was implemented. This research method is descriptive with a qualitative approach. Based on this research, it is revealed that the development of the Islamic religious education curriculum in Indonesia is influenced by changes in the national curriculum and the dynamics that occur in society. The dynamics that occur in the PAI curriculum include: increasing the portion from 25% to 30% in 1975, emphasis on aspects of interfaith tolerance in the 2004 KBK curriculum, PAI occupies top priority over other subjects in the 2013 curriculum. However, the challenge is the emergence of various religious understandings, the lack of readiness of teaching staff, facilities, laboratories, and information technology facilities. The Independent Curriculum provides an opportunity for educators to design lesson plans because this curriculum gives educators the flexibility to apply appropriate methods. However, the challenge is that it requires high creativity from educators.